Diversifikasi Olahan Limbah Kulit Durian Sebagai Komoditas Produk Unggulan Desa Wisata Branjang Menuju Sustainable Independent Economic Revitalization - Zaenuri, Ahmad; Ranihusna, Desti; Brantas Abiprayu, Kris; virma, Made (Journal Of Human And Education (JAHE), 2024)
Revitalizing a Sustainable Independent Economy through diversifying durian skin waste food in Branjang Village is a positive step. Durian, as a typical tropical fruit and a leading commodity in the Branjang Tourism Village, has economic potential that can be further optimized. To be able to develop superior products in the Branjang Tourism Village, this can be done by developing innovative processed products from durian skin waste so that the income obtained can encourage the economic independence of the Branjang Village community in a sustainable manner. Durian fruit farmers in Branjang Village have not been able to make maximum use of durian skin waste management which has the potential to bring in "additional income" apart from selling durian fruit. Not only durian flesh can generate profits, but by utilizing various processed foods from durian skin waste it will continue to increase and improve the economy for the people of Branjang Village. To support the success of this community service program, synergy is needed from the stakeholders involved so that the management of unused durian skin waste can be functional and have economic value for the community around Branjang Village.The Service Team proposes a solution to overcome the problems mentioned above by providing assistance to durian fruit farmers regarding techniques for managing durian skin waste so that they have the skills to produce a variety of quality processed innovative products by utilizing durian skin waste in order to further increase market awareness and ensure product quality. Processed from durian skin waste has high competitiveness and is an economic source towards financial independence. Collaboration and coordination with related parties such as agricultural research institutions, local government and non-governmental organizations is required to support project implementation.The method used in this community service includes 3 activities, namely Counseling and Workshops, Skills training and HR capacity development, Personal Communication